Pengaruh Konsentrasi dan Interval Waktu Pemberian Flower Inducer terhadap Pembungaan Kopi Robusta - Puspita, Anggita; Kartika, Kartika; Zasari, Maera (Universitas Lampung, 2024)
Coffee is a leading commodity in Indonesia because it can increase people's income and foreign exchange. Coffee production can be affected by flowering. Flowering can be done by giving flower inducer, a flower inducer solution containing nutrients and Sitokinin. This study aims to investigate the influence of concentration and timing of flower inducer solution application on the flowering of robusta coffee plants. The research was conducted in Petaling Banjar Village, Bangka Regency, from January to May 2023, using a split-plot experimental design with a randomized block design, repeated four times. The main plots were the weekly and bi-weekly time intervals, and the subplots were the concentrations of Flower Inducer, namely 0 ml/liter, 10 ml/liter, 20 ml/liter, and 30 ml/liter. The results showed that the concentration of flower inducing solution significantly increased the number of silver primordia, the number of perfasciculus primordia, and the period of primordia emergence. A concentration of 20 ml/liter is the best concentration that induces coffee primordia and flowers. Keywords : Coffee, flowering, concentration, sitokinin